Development of a Novel Fully Passive Treadmill Training Paradigm for Lower Limb Therapeutic Intervention - M. Saiful Huq; M. O. Tokhi (Applied Bionics and Biomechanics)
A simulation based study of a completely new form of body-weight supported treadmill training (BWSTT) technique which is fully passive in nature is presented in this paper. The approach does not require any powered means at the lower limbs and is implemented using a combination of coordinated joint locking/unlocking and flexible torque transfer mechanisms. The hip extension pertaining to the stance phase of the gait cycle is achieved through the stance foot being literally dragged by the treadmill belt while the required manoeuvring of the trunk is expected to be accomplished by the voluntary arm-support from the subject. The swing phase, on the other hand, is initiated through appropriately coupling the swing knee with the contralateral extending hip and eventually achieve full knee extension through switching the treadmill speed to a lower value. Considering adequate support from the able arms, the process effectively turns the frictional force at the foot-treadmill belt interface into an agent causing the required whole body mechanical energy fluctuation during the gait cycle.